2022
DOI: 10.1002/14651858.cd008080.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic corticosteroids for sudden sensorineural hearing loss

Abstract: Intratympanic corticosteroids for sudden sensorineural hearing loss (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 141 publications
0
18
0
Order By: Relevance
“…5 Many studies have compared the 2 treatment methods, and according to a recent Cochrane review, there was no difference in treatment outcomes between SS and ITS as primary therapy. 6 However, recent results have shown that SS and ITS combination therapy is superior to SS monotherapy. 5,6 The combination of SS and ITS using different routes to the inner ear has the advantage of maximizing the steroid concentration in the inner ear, which may lead to better outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Many studies have compared the 2 treatment methods, and according to a recent Cochrane review, there was no difference in treatment outcomes between SS and ITS as primary therapy. 6 However, recent results have shown that SS and ITS combination therapy is superior to SS monotherapy. 5,6 The combination of SS and ITS using different routes to the inner ear has the advantage of maximizing the steroid concentration in the inner ear, which may lead to better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, recent results have shown that SS and ITS combination therapy is superior to SS monotherapy. 5,6 The combination of SS and ITS using different routes to the inner ear has the advantage of maximizing the steroid concentration in the inner ear, which may lead to better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of topically delivered medications with effects on the inner ear are widely used in routine clinical practice. These include aminoglycosides for the treatment of Meniere’s disease ( Basura et al, 2020 ) and the therapeutic use of corticosteroids, e.g., in idiopathic sudden sensorineural hearing loss ( Chandrasekhar et al, 2019 ; Dahm et al, 2021 ; Plontke et al, 2022 ). In the scope of local drug delivery to the inner ear, various medications such as antibiotics, steroids, antioxidants, biologicals (Roemer 2017), and promising gene or stem cell therapy alternatives are explored today ( Staecker and Rodgers, 2013 ; Warnecke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic steroid treatment (intravenous or peroral) is the mainstay therapy for ISSNHL 5,6 . However, intratympanic (IT) steroid injection has been indicated as an alternative to systemic steroid treatment for ISSNHL 7,8 . Some studies have reported higher rates of hearing recovery in patients with ISSNHL receiving both systemic steroid treatment and IT steroid injection than in those receiving systemic steroids alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%